Culturally Effective Organization: Revisiting the Role of Employers in Workforce Development in Kathmandu Valley - Lamsal, Aliya; Pradhan, Radhe Shyam (Nepalese Journal of Business, 2025)
This study examines the culturally effective organization: revisiting the role of employers in workforce development in Kathmandu Valley. Workforce development is the dependable variables. The independent variables are job security, organization culture, training and development, cross-cultural competence, recognition and rewards, and leadership styles. The study is based on primary data with 165 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and the culturally effective organization and workforce development in Kathmandu Valley. The study showed that leadership styles have a positive impact on workforce development. It indicates that better leadership styles lead to increase in workforce development. Likewise, recognition and rewards have a positive impact on workforce development. It indicates that better recognition and rewards leads to increase in workforce development. Similarly, cross-cultural competence has a positive impact on workforce development. It means that cross-cultural competence in the organization leads to increase in workforce development. Moreover, training and development has a positive impact on workforce development. It indicates that better the training and development, higher would be the workforce development. In addition, organization culture has a positive impact on workforce development. It reveals that better the organization culture, higher would be the workforce development. Likewise, job security has a positive impact on workforce development. It indicates that increase in job security leads to in-crease in workforce development.